Factor influencing road kill mortality of birds: A review - Dupty Ram; Naveen Tholia (The Bioscan, 2025)
Roads exert several negative and adverse effects on the survival of various animals and ecosystem health, including mortality, injury, habitat fragmentation, habitat isolation and enhancement of noise and chemical pollutants. These factors significantly affect wildlife survival, including that of avian species. Bird species such as scavenging raptors, corvids, and other insectivorous, granivorous and omnivorous species are attracted to roads for foraging and finding food resources. Birds drawn to roads are often startled by approaching vehicles, and such behavioral responses can result in bird fatalities. High speed and traffic volume also influence the mortality patterns of birds due to road vehicle collisions. Larger birds are more susceptible to vehicle collisions than smaller birds.